Effect of shallot peel extract in tofu to detect the presence of formaldehyde - Rantesalu, Agnes; Rohi Bire, Winioliski L. O.; Tangkelangi, Marni; Susilawati, Ni Made (Public Health of Indonesia, 2022)
Background: The prohibition of the addition of formalin in food is carried out because it is dangerous to health. People generally find it challenging to carry out formalin checks on food, which are usually carried out in laboratories because they use chemicals. Another way to test formalin can use natural ingredients that contain anthocyanins. Anthocyanins are a group of pigments, namely flavonoids. These flavonoids are commonly found in plant parts such as fruits and flowers and other parts such as the skin of shallots. Objective: This study aimed to determine the formalin test with shallots peel extract. Methods: An experimental research design was used in this study using colorimetric, which took anthocyanin extract from the skin of the shallots, and the extract was tested again on formalin tofu to see the color change. Results: Shallots peel extract was tested with an Ultraviolet Visible spectrophotometer instrument, and the results showed the presence of anthocyanins in the extract. Conclusion: Formalin testing with shallots peel extract can be done, but we must pay attention to the extraction process so that maximum results can be obtained.